(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2025)
Microplastics (MPs) are pervasive pollutants in marine environments, posing significant threats to ecosystems and human health. This study investigates the accumulation of MPs in Saccostrea cucullata (Rock Oysters) along the West coast of Sri Lanka from August 2021 to July 2022. Six sampling sites were selected to represent areas with varying anthropogenic activity, such as urbanization and tourism. MPs were extracted using alkaline digestion, and identified through hot needle tests and Fourier-Transform Infrared (FTIR) spectroscopy. The results revealed significant spatial variations in MPs concentrations, with the highest mean concentration recorded at Galleface (5.11 ± 2.2 MPs/g w.w.) and the lowest at Negombo Beach (2.60 ± 0.77 MPs/g w.w.). Filamentous blue particles were the most common, and particles smaller than 1 mm comprised nearly 25% of the total MPs. Seasonal factors, particularly the monsoon, influenced the temporal distribution of MPs. This study underscores the urgent need for pollution mitigation strategies, including waste management interventions and public awareness, to protect marine ecosystems and safeguard seafood safety in Sri Lanka.